2016
DOI: 10.1371/journal.pone.0159404
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Breakage in Specific Chromosome Bands 6 Years after Acute Exposure to Oil

Abstract: BackgroundThe identification of breakpoints involved in chromosomal damage could help to detect genes involved in genetic disorders, most notably cancer. Until now, only one published study, carried out by our group, has identified chromosome bands affected by exposure to oil from an oil spill. In that study, which was performed two years after the initial oil exposure in individuals who had participated in clean-up tasks following the wreck of the Prestige, three chromosomal bands (2q21, 3q27, 5q31) were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…Furthermore, the genome-wide study of hot spots of DNA double-strand breaks in human cells 37 not surprisingly show a strong correlation not least with the presently studied radiation-induced breaks, the CpG density and the Hap Map data. Similarly, the recent study of breakage in specific chromosome bands after acute exposure to oil and benzene show similar correlations and close association to fragile sites 38 . The recent genome wide study of p53 pathway cancer related Single Nucleotide Polymorphisms and expression quantitative trait loci 39 both agree very well with the presently described radiation-induced Chromatid Breakage points and both types of Fragile Sites.…”
Section: Recent Related Studiessupporting
confidence: 63%
See 2 more Smart Citations
“…Furthermore, the genome-wide study of hot spots of DNA double-strand breaks in human cells 37 not surprisingly show a strong correlation not least with the presently studied radiation-induced breaks, the CpG density and the Hap Map data. Similarly, the recent study of breakage in specific chromosome bands after acute exposure to oil and benzene show similar correlations and close association to fragile sites 38 . The recent genome wide study of p53 pathway cancer related Single Nucleotide Polymorphisms and expression quantitative trait loci 39 both agree very well with the presently described radiation-induced Chromatid Breakage points and both types of Fragile Sites.…”
Section: Recent Related Studiessupporting
confidence: 63%
“…In average 33% of the common RIBs are collocated with 41% of the FSs respectively, and then practically always in regions of elevated recombination, MLH1 immunofluorescence and chiasma density as seen in Fig 6. The observed large-scale correlation between HapMap recombination sites, chiasma, MLH1 immunofluorescence and highly probable RIBs as seen in Figures 2-6 is striking, even though there seems too be some local deviations. This may also be expected due to use of different population averages in the former datasets, such as when using germ cells from males or females and cells from other tissues, but also due to the wide range of genomic variability over the human genome and the associated genomic instability and hyper mutation in human cancers [32][33][34][35][36][37][38][39][40][41][42][43][44] . In breast cancer patients with poor prognosis 23 on average 69% of the CNCs are located at X-ray RIBs covering less than 20% of the genome, whereas 49% of the CNCs are located in the common and rare FS regions covering about 27% of the genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted 1.5 years [ 13 ] after the spill, the oxidative DNA stress marker levels, which could be indicative of cancer risk, were higher in the high-exposure group than in the low-exposure group; the effect persisted for 6 years after the spill [ 14 ]. Chromosome damage was observed among fishermen in studies conducted two and six years after the Prestige oil spill in Spain [ 15 , 16 , 17 ], and cancer risk modeling was performed after the British Petroleum Deepwater Horizon (BPDH) oil spill in the United States of America (USA) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A long-term genotoxic study, conducted in 52 exposed and 23 non-exposed individuals, showed that structural alterations remained high in exposed individuals, although the association with the exposure to the oil spill could not be substantiated because there was a relevant increase of structural alterations in nonexposed individuals 15 . Nevertheless, 2p23 and 2q23 chromosome bands were only detected in exposed individuals 16 The main results of the SEPAR-Prestige Study are summarised in table 2.…”
Section: Major Findings Of the Separ-prestige Studymentioning
confidence: 99%